Evaluating the performance of Arabic language teachers and female teachers in the light of the evaluation criteria based on performance for the preparatory stage (Journal of the College of Basic Education, 2022)
The aim of the current research is to know (evaluating the performance of Arabic language teachers and female teachers in light of the evaluation criteria based on performance for the preparatory stage). For the academic year 2021-2022, their number is (2007) a teacher and a teacher, The researcher randomly chose the research sample, which amounted to (90) teachers and schools distributed over the six districts by (15) teachers and schools from each district. A group of arbitrators and the note card included (58) criteria, distributed over four areas: Planning (15) standards, teaching aids, educational techniques, and educational activities (12) standards, implementation, and interaction within the classroom environment between teacher and student (17) standards, evaluation, processes and outcomes (14) standards, and after data collection and statistical analysis of results using weighted mean and percentage weight. The researcher reached several results, including The evaluation domain, processes, and outcomes (ranked first with a weighted mean of (2.17)), and weight percentile (72.07), The field (educational means, techniques, and educational activities) ranked last with a weighted mean (1.99), and a percentile weight (66.25), and in light of the results, the researcher reached several conclusions, including The performance of the preparatory stage represented (55.17%) of the evaluation criteria based on performance, The criteria are not achieved in evaluating the performance of Arabic language teachers and female teachers in the light of the evaluation criteria based on performance for the preparatory stage, a percentage of (44.83%) of the evaluation criteria are based on performance, and the researcher also made several recommendations and suggestions.